Literature review on factors associated with the incidence of pulmonary TB - Feriany Said (International Journal of Health Science and Technology, 2023)
Tuberculosis is a disease that is easily transmitted and shows an increase in the number of new cases and the number of deaths caused by pulmonary TB.  Indonesia is included in the top three countries with the highest caseload ratings in the world, after India and China, with 824,000 sufferers (WHO, 2021).  In poor countries, pulmonary TB deaths account for 25% of all preventable deaths. This study aimed to find out the literature review of factors related to the incidence of pulmonary TB. The research method uses a literature review with a database, namely google scholar. The inclusion criteria used include the dependent variable of pulmonary TB incidence, with a cross-sectional study design. A total of 6 national journals that have been analyzed explain a significant relationship between nutritional status, age, sex, and environmental factors with the incidence of pulmonary TB. This research’s contribution needs to eradicate pulmonary TB through improving family nutrition and interventions in the physical environment, especially environmental sanitation.